ANALYSIS OF METAL CONTENT OF Zn, Cr and Cu IN BROWN ALGAE (Sargassum sp.) IN THE WATERS OF BUNGUS, PADANG PROVINCE OF WEST SUMATERA - Febeyessy Aritonang; Irvina Nurrachmi; Thamrin Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in July 2018 with the aim to determine the metal content of Zn, Cr and Cu in brown Algae (Sargassum sp.) From Bungus Waters of West Sumatra Province and to determine the value of Metal pollution index (MPI) in Bungus Waters of West Sumatra Province.Determination of sampling location using purposive sampling, namely by considering the state of the research area. Sampling was carried out in areas with relatively different anthropogenic activities and analysis of heavy metal content was carried out at the Marine Chemistry Laboratory, Faculty of Fisheries and Marine, University of Riau. The results showed that the Zn metal content in brown algae ranged from 55,033 - 70,250 µg / g, where the highest concentrations were at Station 3 and the lowest at Station 1. The concentration of Cr metal in brown algae ranged from 18,500 - 32,833 µg / g, where the highest concentration was found in Station 3 and the lowest at Station 1. The concentration of Cu in brown algae ranges from 2,833 - 7,500 µg / g, where the highest concentration is at Station 3 and the lowest at Station 1. The MPI value of Bungus Waters of West Sumatra Province is 19.44, the value is still normal when compared with research conducted in other regions using Algae samples.Keywords: Zn, Cr and Cu metals, Brown Algae (Sargassum sp.), Bungus waters